2023
DOI: 10.3390/cancers15235653
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling and Therapeutic Insights into Differentially Expressed Genes in Hepatocellular Carcinoma

Wesley Ladeira Caputo,
Milena Cremer de Souza,
Caroline Rodrigues Basso
et al.

Abstract: Background: Drug repurposing is a strategy that complements the conventional approach of developing new drugs. Hepatocellular carcinoma (HCC) is a highly prevalent type of liver cancer, necessitating an in-depth understanding of the underlying molecular alterations for improved treatment. Methods: We searched for a vast array of microarray experiments in addition to RNA-seq data. Through rigorous filtering processes, we have identified highly representative differentially expressed genes (DEGs) between tumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Sha et al showed that glycosyltransferase (GT)-based GT score was associated with GT expression and neuroblastoma (NB) prognosis, disialoganglioside phenotype, and immune infiltration, providing new evidence for predicting NB prognosis and response to immunotherapy [ 39 ]. By using in silico approaches, Caputo et al identified hub genes and transcription factors including AURKA , CCNB1 , CDK1 , RRM2 , and TOP2A as promising candidates for potential drug testing [ 54 ]. Huang et al found that POLE2 , GABARAPL1 , PIK3R1 , NDC80 , and TPX2 play critical roles as potential biomarkers to enhance the immunotherapeutic role of PD-L1 inhibitors [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sha et al showed that glycosyltransferase (GT)-based GT score was associated with GT expression and neuroblastoma (NB) prognosis, disialoganglioside phenotype, and immune infiltration, providing new evidence for predicting NB prognosis and response to immunotherapy [ 39 ]. By using in silico approaches, Caputo et al identified hub genes and transcription factors including AURKA , CCNB1 , CDK1 , RRM2 , and TOP2A as promising candidates for potential drug testing [ 54 ]. Huang et al found that POLE2 , GABARAPL1 , PIK3R1 , NDC80 , and TPX2 play critical roles as potential biomarkers to enhance the immunotherapeutic role of PD-L1 inhibitors [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…To compare the mRNA expression differences of hub genes between HCC cancerous liver tissues and corresponding adjacent non‐tumor liver tissues (histologically normal, adjacent to the tumor but beyond the observed aberrations) 42 , 43 and to evaluate their prognostic value, the Gene Expression Profiling Interactive Analysis (GEPIA; http://gepia.cancer‐pku.cn/ , accessed on 12 May 2024) platform 44 and the University of ALabama CANcer (UALCAN; https://ualcan.path.uab.edu/ , accessed on 12 May 2024) interactive web portal 45 was used. The correlation between mRNA expression of hub genes and the clinical stage of liver cancer patients, as well as protein expression encoded by hub genes, were also analyzed by UALCAN.…”
Section: Methodsmentioning
confidence: 99%